Social cognition assessment in Chinese adults with mild cognitive impairment: a scoping review - Yan Liu; Chungui Zheng; Jianting Cao; Qinyu Guo; Jieting Hu; Yufei Lin; Ziping Pang; Xinran Song; Tiantian Zhai; Fangping Dang (Frontiers in Public Health, 2026)
Background Social cognition is a core cognitive domain that is impaired in mild cognitive impairment (MCI), yet the availability and utility of assessment tools for this population in China remain unclear. Objective This scoping review aimed to systematically map the current evidence on social cognition assessment tools for Chinese older adults with MCI, and to identify gaps in the literature concerning cultural adaptation and psychometric validation. Methods We systematically searched CNKI, CBM, Wanfang, Weipu, PubMed, and Web of Science up to 23 June 2026. We included original studies that assessed social cognition tools in Chinese MCI patients with controls, extracted data on study design, tools, domains, and results, and conducted a narrative synthesis. Results Six studies met the inclusion criteria, comprising 198 MCI participants and 197 healthy controls. The assessment tools covered three social cognition domains: empathy, facial emotion recognition, musical emotion recognition, and social perception. All studies reported significant impairments in MCI, particularly in negative emotion recognition (disgust, sadness, fear) and empathy. However, none reported reliability coefficients (e.g., Cronbach's α) or established diagnostic cut-off scores for the Chinese MCI population. Sample sizes were small (range 19–59 per MCI group), and all studies were single-center. Conclusion Evidence suggests that Chinese MCI patients show social cognition deficits across multiple domains, yet current tools are insufficiently validated and culturally adapted. Future studies may consider multi-center validation, establishing normative data and cut-offs, and developing culturally relevant instruments for China.